Facile CO Cleavage by a Multimetallic CsU2 Nitride Complex. Issue 40 (6th September 2016) - Falcone, Marta; Kefalidis, Christos E.; Scopelliti, Rosario; Maron, Laurent; Mazzanti, Marinella
Abstract: Uranium nitrides are important materials with potential for application as fuels for nuclear power generation, and as highly active catalysts. Molecular nitride compounds could provide important insight into the nature of the uranium–nitride bond, but currently little is known about their reactivity. In this study, we found that a complex containing a nitride bridging two uranium centers and a cesium cation readily cleaved the C≡O bond (one of the strongest bonds in nature) under ambient conditions. The product formed has a [CsU2 (μ‐CN)(μ‐O)] core, thus indicating that the three cations cooperate to cleave CO. Moreover, the addition of MeOTf to the nitride complex led to an exceptional valence disproportionation of the CsU IV –N–U IV core to yield CsU III (OTf) and [MeN=U V ] fragments. The important role of multimetallic cooperativity in both reactions is illustrated by the computed reaction mechanisms. Abstract : The power of cooperation : A heteropolymetallic uranium nitride with a CsU IV –N–U IV core effected complete cleavage of the strong C≡O bond of carbon monoxide under ambient conditions (see scheme). The reaction led to the formation of a CN − ligand, which could be alkylated readily to afford organic nitriles. The important role of multimetallic cooperativity in these reactions was identified by computation of the reaction mechanisms.